Establishing basis for funnel approach in research: Using ontology to examine electronic payment system from the view of business process reengineering - Abubakar, Faruq Muhammad; Ahmad, Hartini; Baharin, Shamsuddin (2013)
Researchers are often been confronted with the dilemma of providing a clear linkage among otherwise differing entities, because it has become a general requirement for researchers to view phenomenon from a broader to a narrowed perspective.The objective of this paper is to create connection between Business Process Re engineering (BPR) and Electronic Payment System (EPS) and make way for researchers to build upon this method to make similar connection in the future.Based on comprehensive literature review and use of ontology approach, it was found that people, process, and technology are the basic components of BPR, whereas technology is categorized into soft and hard technology.Within the soft technology there are different types, which include business technology, social technology, military technology etc.Finally, further linkage was provided between business technology and e-payment systems.This paper pioneered the use of ontology approach to provide connections among st those entities.